Surface elevation changes of the Patagonian Icefields: Insights from an ICESat(-2) crossover analysis - F. Suad Corbetta; F. Suad Corbetta; A. Richter; A. Richter; E. Marderwald; E. Marderwald (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The Patagonian Icefields, located in southernmost South America, are the biggest extrapolar concentration of ice in the southern hemisphere. As such, they are of strategic and environmental importance, which will increase even more as freshwater reserves become scarcer around the world. This encourages a detailed study of the conditions and temporal evolution of the icefields, determining with high precision the area, volume and mass changes of the glaciers that compose the icefields. However, glaciological in-situ measurements are unable to provide results representative for the entire region, because of the difficult access to the icefields, harsh physical conditions, and the large spatio-temporal variability among the Patagonian glaciers. While all regional scale studies of the Patagonian Icefields find a significant mass loss, different methods arrive at different rates. This calls for the inclusion of additional, independent observation techniques, and laser satellite altimetry is a prime candidate for it. Satellite altimetry, traditionally employed for sea-level monitoring, determines accurate surface elevations along the ground track of the satellite's repeat-orbit. Therefore, most altimetry missions do not provide a continuous areal coverage, impeding the separation between spatial and temporal elevation changes. Crossover analysis isolates temporal variations in the intersections of tracks observed at different epochs. In this work, ICESat and ICESat-2 data is used, and a crossover analysis is performed, in order to determine seasonal and long-term elevation changes of the ice surface of the Patagonian Icefields. The results are presented and discussed, along with an explanation of the applied methods.